North Andean origin and diversification of the largest ithomiine butterfly genus - Lisa De-Silva, Donna (Sci Rep, 2017)
The Neotropics harbour the most diverse flora and fauna on Earth. The Andes are a major centre of diversification and source of diversity for adjacent areas in plants and vertebrates, but studies on insects remain scarce, even though they constitute the largest fraction of terrestrial biodiversity. Here, we combine molecular and morphological characters to generate a dated phylogeny of the butterfly genus Pteronymia (Nymphalidae: Danainae), which we use to infer spatial, elevational and temporal diversification patterns. We first propose six taxonomic changes that raise the generic species total to 53, making Pteronymia the most diverse genus of the tribe Ithomiini. Our biogeographic reconstruction shows that Pteronymia originated in the Northern Andes, where it diversified extensively. Some lineages colonized lowlands and adjacent montane areas, but diversification in those areas remained scarce. The recent colonization of lowland areas was reflected by an increase in the rate of evolution of species’ elevational ranges towards present. By contrast, speciation rate decelerated with time, with no extinction. The geological history of the Andes and adjacent regions have likely contributed to Pteronymia diversification by providing compartmentalized habitats and an array of biotic and abiotic conditions, and by limiting dispersal between some areas while promoting interchange across others.